1972
DOI: 10.1085/jgp.60.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Dark Ionic Flux and the Effects of Light in Isolated Rod Outer Segments

Abstract: We have determined the permeability properties of freshly isolated frog rod outer segments by observing their osmotic behavior in a simple continuous flow apparatus. Outer segments obtained by gently shaking a retina are sensitive but nonideal osmometers; a small restoring force prevents them from shrinking or swelling quite as much as expected for ideal behavior. We find that Na+, Cl-, No, glycerol, acetate, and ammonium rapidly enter the outer segment, but K+, SO, and melezitose appear impermeable. The Na fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
83
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(96 citation statements)
references
References 39 publications
13
83
0
Order By: Relevance
“…The studies presented above, which are generally consistent with the earlier papers (Werblin 1975;Cervetto et al 1977), generate two important questions: (1) how can the lack of a reversal potential (Werblin, 1975, and here), or a reversal potential more negative than the dark level (Lasansky & Marchiafava, 1973;Cervetto et al 1977), be reconciled with evidence for a light-elicited sodium conductance change (Hagins, Penn & Yoshikami, 1970;Yoshikami & Hagins, 1971;Korenbrot & Cone, 1972) and, (2) is it legitimate to look for a conductance change when recording from a single rod when the rods may be strongly coupled (Schwartz, 1976)? Some insight into the resolution of these questions can be gained by studying the coupling of the components of an individual rod, and the coupling between rods, as outlined below.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The studies presented above, which are generally consistent with the earlier papers (Werblin 1975;Cervetto et al 1977), generate two important questions: (1) how can the lack of a reversal potential (Werblin, 1975, and here), or a reversal potential more negative than the dark level (Lasansky & Marchiafava, 1973;Cervetto et al 1977), be reconciled with evidence for a light-elicited sodium conductance change (Hagins, Penn & Yoshikami, 1970;Yoshikami & Hagins, 1971;Korenbrot & Cone, 1972) and, (2) is it legitimate to look for a conductance change when recording from a single rod when the rods may be strongly coupled (Schwartz, 1976)? Some insight into the resolution of these questions can be gained by studying the coupling of the components of an individual rod, and the coupling between rods, as outlined below.…”
Section: Resultssupporting
confidence: 71%
“…Although there is good evidence that the light response is initiated by a conductance decrease at the rod outer segment (Brown & Pinto, 1974;Hagins, Penn & Yoshikami, 1970;Korenbrot & Cone, 1972; Sillman, Ito & Tomita, 1969), it has been suggested that the distributed nature of light-elicited current through the rod network might obscure the intracellular measurement of this conductance decrease (Schwartz, 1976). Although a light-elicited conductance decrease has been measured in some preparations (Toyoda, Nosaki & Tomita, 1969;Toyoda, Hashimoto & Anno, 1970), no conductance change was measured in mudpuppy (Werblin, 1975) and a conductance increase has been measured in tiger salamander (Lasansky & Marchiafava, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…In constructing a model for phototransduction-induced osmotic swelling of the rod OS, we first considered the consequences of water influx. As moderate osmotic perturbation alters only rod OS length and not width (40,41), length increases can be readily converted into volume changes and influx rates. The swelling response showed a light dependence consistent with maximal activation of Gα t , reaching a saturated amplitude in response to light that isomerizes ∼1 R* per Gα t (Figs.…”
Section: Maximal Activation Of Phototransduction Increases Rod Osmentioning
confidence: 99%
“…Because most proteins can act as elastic elements (50), it is reasonable to hypothesize that such disc-to-disc "linkers" serve as springs that resist swelling, affording some protection of the rod OS from stimulus-induced osmotic overload. As rod OSs primarily swell axially in response to osmotic challenge (40,41), if the OS has an elastic response, the steadystate elongation should obey Hookes' law…”
Section: Estimating the Spring Constant Of An Elementary Rod Os Elasticmentioning
confidence: 99%
“…The absorption of light causes photoisomerization of rhodopsin in the rod disk membrane and a subsequent decrease in the Na conductance ofthe plasma membrane and in the Na conductance of the plasma membrane of the rod outer segment (Yoshikami & Hagins, 1971; Korenbrot & Cone, 1972;Brown & Pinto, 1974). Little is known about the events that intervene between the absorption of photons in rod disks and changes in plasma membrane Na conductance, but it is thought that light induces a change in the concentration of an intracellular messenger (Baylor & Fuortes, 1970) which diffuses from the disk membrane to the plasma membrane and reduces the Na conductance.…”
Section: Introductionmentioning
confidence: 99%